Socio-Psychological Analysis of The Formation of Honesty Vaccine In Civil Servants - Nurdinov, Javharbek (Pubmedia Social Sciences and Humanities, 2025)
This study explores the concept of an "honesty vaccine" and its role in fostering integrity among civil servants. The research investigates various socio-psychological mechanisms, including ethical education, social responsibility, and institutional control, to strengthen resistance against corruption. Utilizing a qualitative approach, the study reviews global best practices in promoting transparency and public trust in governance. The results suggest that effective training programs, strict accountability measures, and a culture of ethical behavior significantly enhance civil service integrity.